Pannwitz, Hofmannsthal und Österreich: [Pannwitz, Hofmannsthal and Austria] (Studia theodisca, 2025)
This study deals with the relation of the German poet and philosopher Rudolf Pannwitz to Austria in the period 1917-1922, as he was witnessing the dissolution of the Austrian-Hungarian Empire while living in Austria himself. His reflections on Austria’s present and possible future can be traced back in his correspondence with Hugo von Hofmannsthal, an outstanding representative of the Austrian culture at that time, but also in some of the essays he published in the period. An important aspect of the context in which Pannwitz regarded the future of Austria, was his personal contact with Czech intellectuals that resulted in the publication of his book on «The spirit of the Czechs» (1919). Finally,  the study aims to place Pannwitz’s intellectual relation to Austria and Bohemia in the context of his view of a European future.